Words Made Flesh : Formations of the Postsecular in British Romanticism - Dempsey, Sean, 1974- (Book collections on Project MUSE., 2022)
"Words Made Flesh demonstrates how the Romantic poets Samuel Taylor Coleridge, John Keats, and Percy Bysshe Shelley and the novelist Jane Austen affect, mediate, and ultimately alter our sense of self and embodiment in ways that not only feel profound but also have lasting effects on readers' affective, political, and spiritual lives. The author draws in particular on secular and postsecular studies, affect theory, and media studies"--